Data Fast Transmission Method in Wireless Vehicle Ad-hoc Network - Niknamian, Sorush (Journal of Applied Science, Engineering, Technology, and Education, 2019)
In vehicular ad hoc networks, the current method does not consider the delay of data transmission, resulting in slower vehicle data transmission speed. A vehicle data transmission method based on backbone network is proposed in this paper. Firstly, the characteristics of vehicle ad hoc network are analyzed. Based on the statistics of the road, the vehicle cluster is composed of the vehicles parking on the roadside and no roadside according to the different directions of the vehicle driving. The backbone network is constructed on the basis of the cluster of vehicles, and the data transmission between the vehicles is implemented by the data transmission method of overlay network. This method can overcome the disadvantages of traditional data transmission methods, improve the efficiency of on-board data transmission, and complete the research on fast data transmission method in wireless vehicle ad hoc network. The experimental results show that the proposed method can achieve higher data transmission success rate with lower data transmission overhead and smaller transmission delay.